Impact of Biologic and Conventical Synthetic DMARDs on Serum Coenzyme Q10 and Malondialdehyde in Rheumatoid Arthritis Patients - Mohsin, Nagham Y.; Saleh, Basil O.; Gorial, Faiq I. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune illness. Oxidative stress such as Malondialdehyde plays a major role in the pathophysiology of RA while antioxidants such as Coenzyme Q10 play protect role against inflammation.Objectives: The study aimed to compare serum concentrations of Coenzyme Q10 and Malondialdehyde in rheumatoid arthritis patients and healthy controls and to evaluate how different types of treatment (biologics and chemotherapy) influence serum levels of them in this disease. Methods: The case-control study was conducted on 88 individuals (60 had been diagnosed with rheumatoid arthritis and 28 healthy as (Controls). The patients were recruited from the Rheumatology Unit of Baghdad Teaching Hospital in Baghdad, Iraq, during the period from November 2024 to March 2025. They were subdivided into four groups according to the type of treatment (biology, biology & chemotherapy, biology & other, chemotherapy & other). Serum investigations included measurements of anti-cyclic citrullinated peptide antibody, high-sensitivity C-reactive protein, Coenzyme Q10, and Malondialdehyde, measured by using Enzyme linked immunosorbent assay technique.Results:  The study found that the mean (±SD) values of Malondialdehyde were significantly highly increased (705.77 ± 168.83, p